PENGARUH MODEL KEPEMIMPINAN TERHADAP KINERJA PEGAWAI KELURAHAN BRANG BIJI SUMBAWA BESAR - Eda Elvazira; Heni Lestari; S Syafruddin (Pusat Riset dan Publikasi, 2022)
Employee performance is one of the success factors of an organization in achieving a goal. There are so many factors that support the performance of an employee, including the leadership model factors that indirectly shape the character of an employee's performance. The leadership model intended in this study is the Autocracy, Democracy and Laizzes-Faire leadership model. The purpose of this study was to determine the effect of the leadership model on the performance of the employees of the Brang Biji Sub-district, Sumbawa Besar. This research was conducted in Brang Biji Village with a population of 15 people and the entire population was used as the object of research. The techniques used in data collection are questionnaire techniques and documentation techniques. Analysis of the data used in this study is Multiple Linear Regression. From the results of the study, it was found that there was a significant effect of the autocratic leadership model, democratic leadership model, and Laizzes-Faire leadership model on the performance of Brang Biji village employees, either partially or simultaneously.